Infâncias possíveis: ser criança na favela do Gonzaga e no condomínio Jardim Paulista - Begnami, Patricia dos Santos (2014)
This study aims to contribute to the anthropological debates regarding the notions of childhood and child in the scope of urban anthropology and anthropology of children. Through ethnography with children in two different social contexts - the Gonzaga favela (São Carlos-SP) and the Jardim Paulista condominium (Araras - SP) - I analyze the particularities and the plurality of the ways of being a child through the experiences and life of these agents in such urban spaces. The goal is to speculate on the multiplicity of possible childhood notions, paying attention to the ways in which such notions are linked to different definitions of families, house, street, risks and possible agencies.